The effect of the Video Assistant Referee on referee's decisions in the Spanish LaLiga. Issue 3 (June 2021) - Lago-Peñas, C; Gómez, MA; Pollard, R
Video Assistant Referee (VAR) was officially introduced into Association Football (Soccer) regulations in 2018. The aim of this study was to examine how the implementation of this technology has modified the play in elite soccer. The sample consists of all 760 matches played in the Spanish LaLiga during the seasons before and after the implementation of the VAR system. The following variables were recorded for each match and half: Fouls, Goals, Oﬀsides, Penalties, Playing time, Red cards and Yellow cards. Match statistics were retrieved from the website of "Whoscored" (www.whoscored.com ). A Mann-Whitney U test and Generalized linear model were used to compare seasons before and after the implementation of VAR. Overall, the findings of the present study showed that the VAR system does not dramatically change the play in elite soccer. Nevertheless: (i) there was a significant decrease in the number of offside after the implementation of VAR; (ii) there was a slight increase in the number of minutes added to the playing time in the first and second half and the full game; and (iii) in most of 70% of all matches, the checks of the match-changing incidents did not lead to review. Moreover, the impact of the VAR system on the game decreases with VAR-only reviews, where the final decision was only based on the communication with the VAR, compared to matches with on-field reviews, where the main referee reviewed the footage on a monitor near the pitch. These findings suggest that to reduce time-wasting and speed up the match, the number of on-field reviews should be reduced.